Effect of Melatonin in Epithelial Mesenchymal Transition Markers and Invasive Properties of Breast Cancer Stem Cells of Canine and Human Cell Lines - Goncalves, Naiane do Nascimento; Colombo, Jucimara; Lopes, Juliana Ramos [UNESP]; Gelaleti, Gabriela Bottaro [UNESP]; Moschetta, Marina Gobbe; Sonehara, Nathalia Martins; Hellmen, Eva; Zanon, Caroline de Freitas [UNESP]; Oliani, Sonia Maria [UNESP]; Pires de Campos Zuccari, Debora Aparecida [UNESP] (Public Library Science, 2016)
Cancer stem cells (CSCs) have been associated with metastasis and therapeutic resistance and can be generated via epithelial mesenchymal transition (EMT). Some studies suggest that the hormone melatonin acts in CSCs and may participate in the inhibition of the EMT. The objectives of this study were to evaluate the formation of mammospheres from the canine and human breast cancer cell lines, CMT-U229 and MCF-7, and the effects of melatonin treatment on the modulation of stem cell and EMT molecular markers: OCT4, E-cadherin, N-cadherin and vimentin, as well as on cell viability and invasiveness of the cells from mammospheres. The CMT-U229 and MCF-7 cell lines were subjected to three-dimensional culture in special medium for stem cells. The phenotype of mammospheres was first evaluated by flow cytometry (CD44(+)/CD24(low)/(-) marking). Cell viability was measured by MTT colorimetric assay and the expression of the proteins OCT4, E-cadherin, N-cadherin and vimentin was evaluated by immunofluorescence and quantified by optical densitometry. The analysis of cell migration and invasion was performed in Boyden Chamber. Flow cytometry proved the stem cell phenotype with CD44(+)/CD24(low)/(-) positive marking for both cell lines. Cell viability of CMT-U229 and MCF-7 cells was reduced after treatment with 1 mM melatonin for 24 h (P<0.05). Immunofluorescence staining showed increased E-cadherin expression (P<0.05) and decreased expression of OCT4, N-cadherin and vimentin (P<0.05) in both cell lines after treatment with 1 mM melatonin for 24 hours. Moreover, treatment with melatonin was able to reduce cell migration and invasion in both cell lines when compared to control group (P<0.05). Our results demonstrate that melatonin shows an inhibitory role in the viability and invasiveness of breast cancer mammospheres as well as in modulating the expression of proteins related to EMT in breast CSCs, suggesting its potential anti-metastatic role in canine and human breast cancer cell lines.